Pencegahan Diare Kalangan Remaja di Pondok Pesantren Al-Jamil Kelurahan Mersi Kecamatan Purwokerto Timur - Anton Suhendro; Dwi Novitasari; Destina Farinda; Aldania Silfianingsih Alimudin; Claudia Pratiwi Kumanireng; Anggi Meli Yani; Sania Wardah; Cita Purnanika; Jaylening Wintri Dao (Yayasan Inspirasi El Burhani, 2023)
Introduction: Diarrhea is a condition in which there is a disturbance in the human digestive tract, characterized by the consistency of watery or liquid stools or feces as well as the frequency of defecation more than three times a day. Many cases of diarrhea can heal on their own and are not dangerous, but diarrhea can disturb the sufferer and can cause complications of certain diseases. Therefore, diarrhea must be treated as soon as possible. Objective: The purpose of this service was to increase knowledge about diarrhea in adolescents. The purpose of this study is to find out the causes of diarrhea, prevent diarrhea, and know the six steps of good and correct hand washing. Method: This public service was conducted by conducting direct counseling on Saturday, July 15, 2023, from 20:00 to 21:30. The target of this counseling was the students of Al-Jamil Islamic Boarding School, with a total of 24 participants. Then, by using lecture, demonstration, redemonstration, and question and answer methods with the media used, namely PowerPoint and leaflets, about prevention of diarrhea and knowing the 6 steps of good and correct hand washing, Result: From this survey, the frequency of diarrhea that occurred in the students of Al-Jamil Islamic Boarding School in the last month was categorized by age. There were 4 students aged 13 years, 3 students aged 14 years, 3 students aged 16 years, and 1 student aged 17 years who experienced diarrhea in the last month. Conclusion: This counseling activity on diarrhea in adolescents runs well and smoothly. There is an increase in adolescent knowledge about diarrhea.